Irreversible Coma clinicopathologic correlations in 79 observations - Jerí, F. Raúl (1969)
Clinical and developmental data of 79 patients suffering from deep coma associated with isoelectric electroencephalogram for at least 24 consecutive hours are presented. The neuropathological study showed that the vast majority had ischemic lesions in the cerebral cortex hiccups field , cerebellum , striatum , thalamus and to a lesser extent , in the brain - stem . Failed to check precise relationship between the clinical manifestations of the specific nerve dysfunction and destruction of neural territories. It was found that the deep coma, cardiorespiratory depression associated with flat electroencephalogram , is incompatible with life . Stopping the methods of resuscitation the patient died a few minutes. The findings of this work with a new definition of death , which takes into account not only the circulatory and respiratory function, functional nervous system activity and the spontaneous EEG are related.